2018
DOI: 10.3390/ijms19123946
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonamide Inhibition Studies of a New β-Carbonic Anhydrase from the Pathogenic Protozoan Entamoeba histolytica

Abstract: A newly described β-carbonic anhydrase (CA, EC 4.2.1.1) from the pathogenic protozoan Entamoeba histolytica, EhiCA, was recently shown to possess a significant catalytic activity for the physiologic CO2 hydration reaction (kcat of 6.7 × 105 s−1 and a kcat/Km of 8.9 × 107 M−1 s−1). A panel of sulfonamides and one sulfamate, some of which are clinically used drugs, were investigated for their inhibitory properties against EhiCA. The best inhibitors detected in the study were 4-hydroxymethyl/ethyl-benzenesulfonam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…In the recent past, CAs belonging to the β -CA family have emerged as potential targets for developing drugs against diseases caused by bacterial and parasitic pathogens. Indeed, several in vitro inhibition studies have shown that the β -CAs from pathogenic bacteria and parasitic pathogens can be inhibited by certain compounds [12,13,14,15,16,17,18,19,20,21,22,23,24]. Among these inhibitors are sulfonamides and their bioisosteres, which are the main classes of CA inhibitors that have been in clinical use for more than 50 years [25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent past, CAs belonging to the β -CA family have emerged as potential targets for developing drugs against diseases caused by bacterial and parasitic pathogens. Indeed, several in vitro inhibition studies have shown that the β -CAs from pathogenic bacteria and parasitic pathogens can be inhibited by certain compounds [12,13,14,15,16,17,18,19,20,21,22,23,24]. Among these inhibitors are sulfonamides and their bioisosteres, which are the main classes of CA inhibitors that have been in clinical use for more than 50 years [25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…These facts and a number of recent publications suggest that cancer-related CAs are, indeed, potential and promising anti-cancer targets [22]. These CAs can be efficiently inhibited using various types of inhibitors, such as 7-aryl-triazolyl-substituted sulfocoumarins [24], acetazolamide [25,26,27,28,29,30,31,32], 6-ethoxy-2-benzothiazolesulfonamide (EZA) [33], benzene sulfonamides [34], 1,3,4-thiadiazole-2-sulfonamide [35], and sulfamide-related compounds [36]. CAs may also be modulated by lncRNAs via the administration of phytochemical compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Carbonic anhydrases (CAs, EC 4.2.1.1) are metalloproteins involved in several metabolic processes [8,9,10,11,12,13,14,15,16,17] either directly, by providing CO 2 /bicarbonate for carboxylating reactions [8,9,12,13], or indirectly, by modulating pH [13,14,15,16,17]. Indeed, CAs convert the neutral molecules CO 2 and water to a weak base (bicarbonate) and a strong acid (hydronium ion) with very high efficacy [8,13].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, in many organisms including bacteria, CAs are the main players in pH homeostasis and related physiologic processes, which are involved in the metabolism, survival and colonization of various niches in which these organisms thrive [18,19,20,21,22,23,24,25]. These processes were mainly investigated for pathogenic microorganisms, such as bacteria [9,13,16,17], protozoa [10,11,21,22] and fungi [17,26]. However, the wide distributions of these enzymes in non-pathogenic Archaea [25] and Bacteria [3,4,6,7,27] make them of interest for understanding crucial biochemical processes connected with metabolism, adaptation to various environmental conditions, and survival in extreme environments.…”
Section: Introductionmentioning
confidence: 99%